The 2025 Torang Muamalah Program to Strengthen the Sharia Economy and Halal MSMEs in Sorong, West Papua - Annisa Mangole (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This study aims to examine the impact of the Torang Muamalah 2025 Program on strengthening the sharia economy and empowering halal MSMEs in Sorong, West Papua. The method used was descriptive qualitative, with data collection techniques through interviews, observation, and documentation. The results indicate that the program has successfully built an inclusive economic ecosystem involving local governments, Islamic financial institutions, Islamic boarding schools (pesantren), and MSMEs. The program provides training, access to Islamic financing, and effective halal certification facilitation to increase the capacity and quality of MSME products. Furthermore, market expansion occurred through participation in the Islamic Economic Festival (FESyar). The program's socio-economic impact, in the form of improved community welfare and new job creation, is significant. In conclusion, Torang Muamalah 2025 is an effective and sustainable model of sharia economic empowerment and can serve as a model for development in other regions. This program not only increases microeconomic capacity but also strengthens the social and spiritual foundations that serve as the foundation for sustainable economic development in West Papua.